Active vibration isolation control platform - YANG TAO; CAI LI; TAN MIN; LIANG ZIZE; MA JIA; LIANG XIAO; HOU ZENGGUANG; LI EN (2011)
The invention discloses an active vibration isolation control platform. The active vibration isolation control platform comprises an active vibration isolation device and an active vibration isolation controller; the active vibration isolation device comprises a lower platform, a midbody and an upper platform; a voice coil motor actuator is arranged between the midbody and the lower platform; a linear variable differential transformer type displacement sensor is arranged between the upper platform and the midbody; and two three-freedom-degree acceleration sensors are arranged on the upper platform and the lower platform respectively. The vibration isolation controller is designed according to a master-slave open type control structure and consists of an upper control computer and a lower execution controller, wherein the upper control computer is a mainframe of an embedded type industrial control computer PC/104; and the lower execution controller is an open-type controller. The active vibration isolation con